A subset of ectomesenchymal chondromyxoid tumours of the tongue show EWSR1 rearrangements and are genetically linked to soft tissue myoepithelial neoplasms: a study of 11 cases. Issue 4 (6th May 2016) - Argyris, Prokopios P; Bilodeau, Elizabeth A; Yancoskie, Aaron E; Trochesset, Denise; Pambuccian, Stefan E; Wetzel, Stephanie L; Shah, Sonal S; Edelman, Morris; Freedman, Paul; Dolan, Michelle; Koutlas, Ioannis G
Abstract : Aims: Ectomesenchymal chondromyxoid tumour (ECT) is a rare, benign intraoral neoplasm showing a predilection for the anterior dorsum of the tongue. The World Health Organization includes ECT in the pathological spectrum of soft tissue myoepithelioma. EWS RNA‐binding protein 1 gene ( EWSR1 ) rearrangement is found in 45% of cutaneous, soft tissue and bone myoepithelial neoplasms, and pleomorphic adenoma gene 1 ( PLAG1 ) aberrations are found in 37% of EWSR1 ‐negative soft tissue myoepitheliomas. The aim of this study was to evaluate the presence of EWSR1 and PLAG1 rearrangements in ECTs. Methods and results: Eleven formalin‐fixed, paraffin‐embedded ECTs were evaluated with fluorescence in‐situ hybridization probes for EWSR1 (22q12) and PLAG1 (8q12). Among the 11 ECTs tested, three (27.3%) showed EWSR1 rearrangement in >15% of tumour cells, whereas eight (72.7%) cases did not show EWSR1 rearrangement. Eight of nine (89%) ECTs showed gain of EWSR1, probably representing gain of all or part of chromosome 22, in a varying proportion of neoplastic cells ranging between 1.4% and 27.9%. PLAG1 rearrangement was not detected in the successfully hybridized tissue sections (7/11). No correlation was observed between the molecular and histopathological findings, such as morphology of the neoplastic cells, the presence of atypia, and matrical type. Conclusions: We identified EWSR1 rearrangement in >25% of ECTs. These results suggest that some ECTs are at least genetically related to myoepithelioma of the soft parts. Finally, PLAG1 aberrations do not appear to be critical in the pathogenesis of ECT of the tongue.